FATORES DE RISCO PARA INCONTINÊNCIA URINÁRIA EM MULHERES PÓS-MENOPAUSA - Martins, Eliara T. C.; Bruisman, Fabiana; Dezordi, Francieli P.; Bertolo, Élvio M.; Berlezi, Evelise M.; Dreher, Daniela Z. (Salão do Conhecimento, 2013)
Resumo